2003
DOI: 10.1016/j.stam.2004.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mg and RE additions on the semi-solid microstructure of a zinc alloy ZA27

Abstract: The effects of 2 mass% Mg and 0.8 mass% RE additions on the microstructural evolution of a Zr modified zinc alloy ZA27 during isothermal holding at semi-solid temperature of 460 8C have been studied by optical microscope and scanning electron microscope. Results show that these two elements all decrease the coarsening rate of solid primary particles, and improve the uniformity of particle size. The addition of Mg greatly decreases the solid fraction, and then increases the distance between particles. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In addition, the behaviours of particle coarsening of these two alloys, together with that of the Zradded ZA27 alloy without the other elements, obey the LSW law after the three semi-solid systems reach their solid-liquid equilibrium states. The additions of these two elements have no visible effect on the shape factor of particles [14].…”
Section: Introductionmentioning
confidence: 95%
“…In addition, the behaviours of particle coarsening of these two alloys, together with that of the Zradded ZA27 alloy without the other elements, obey the LSW law after the three semi-solid systems reach their solid-liquid equilibrium states. The additions of these two elements have no visible effect on the shape factor of particles [14].…”
Section: Introductionmentioning
confidence: 95%
“…Microstructures after heat treatment: The purpose of heat treatment for ZA27 alloy is to eliminate dendritic segregation and abnormal structure [16]. In the present investigation, solid solution heat treatment at 370℃ for 10 hours and quenching in water subsequently offered the alloy of apparent two phase microstructure, leaded to the interconnection of individual original dendrites and the elimination of eutectic structure and ε compound among dendrites.…”
Section: Resultsmentioning
confidence: 76%
“…For example, after treated at 575 • C, 580 • C and 585 • C for 120 min, the measured average size of unmelted primary solid particles in semi-solid experimental alloy is 67 m, 53 m and 48 m, respectively. In addition, it is surprising that the coarsening of unmelted primary solid particles by the mechanisms of coalescence and Ostwald ripening (Czerwinski, 2005;Wang et al, in press;Chen et al, 2003), is not observed under the experimental condition of this paper. At the same time, another surprising result is found from Figs.…”
Section: Semi-solid Microstructural Evolutionmentioning
confidence: 61%